2003
DOI: 10.1103/physrevb.67.020403
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of spin dynamics in closure domain and vortex structures

Abstract: Time-resolved Kerr microscopy is used to study the excitations of individual micron-scale ferromagnetic thin film elements in their remnant state. Thin (18 nm) square elements with edge dimensions between 1 and 10 µm form closure domain structures with 90 degree Néel walls between domains. We identify two classes of excitations in these systems.The first corresponds to precession of the magnetization about the local demagnetizing field in each quadrant, while the second excitation is localized in the domain wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
259
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(280 citation statements)
references
References 20 publications
14
259
1
3
Order By: Relevance
“…6 In this case, the gyrotropic resonance was exploited-a low-frequency mode where the vortex rotates around its equilibrium position. 5,7,8,10 In order to use the resonant properties of the vortex, it has to be brought on its gyrotropic orbit. The time required for this depends on the gyrotropic frequency, which is approximately proportional to the sample's aspect ratio and has typical values of about a gigahertz or below for thin-film elements.…”
Section: Institut Für Festkörperforschung Iff-9 "Elektronische Eigensmentioning
confidence: 99%
“…6 In this case, the gyrotropic resonance was exploited-a low-frequency mode where the vortex rotates around its equilibrium position. 5,7,8,10 In order to use the resonant properties of the vortex, it has to be brought on its gyrotropic orbit. The time required for this depends on the gyrotropic frequency, which is approximately proportional to the sample's aspect ratio and has typical values of about a gigahertz or below for thin-film elements.…”
Section: Institut Für Festkörperforschung Iff-9 "Elektronische Eigensmentioning
confidence: 99%
“…Owing to these potential applications, magnetic vortex structures have received a large amount of experimental and theoretical study during the past ten to fifteen years. One of the most prominent dynamical effects is gyrotropic precession of the vortex core, which has been experimentally [1][2][3][4] observed in thin circular disks. In these systems the vortex core can be forced off-center by an in-plane magnetic field pulse and gyrotropic precession is imaged as spiral motion of the core as it returns to the disk center as a result of dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies with high spatial and temporal resolution have demonstrated that domains, domain walls, and vortices exhibit different excitation spectra. 5,14 Such investigations have mostly focused on small perturbations and on reversible changes in these structures produced by an external field. 15,16 However, in a recent study on cross-tie walls, Neudert et al 17 have reported the creation of new cross ties, i.e., of vortex-antivortex pairs, in response to high-frequency magnetic fields.…”
mentioning
confidence: 99%
“…2 In particular, the magnetic vortex has attracted much interest. [3][4][5][6][7][8][9] An equally fundamental, yet much less studied, magnetic structure is the antivortex, the topological counterpart of the vortex. In the complex structures occurring in extended soft-magnetic films, antivortices can be found almost as frequently as ordinary vortices: they occur in cross-tie domain walls, where they are enclosed by two adjacent vortex structures.…”
mentioning
confidence: 99%